Effectiveness of ‘pocket Mandarin’ for online learning among Mandarin as a foreign language basic learners / Ting Hie Ling … [et al.] - Ling, Ting Hie; Yoke, Soo Kum; Choo, Siang Lay; Ee, Ooi Sing; Peng Hwa, Chong (Universiti Teknologi MARA, 2021)
In the face of difficulties of teaching and learning due to the impact of Covid-19, online lessons have become vital. This has also affected the teaching of Mandarin as a foreign language at universities. Since Mandarin is considered as a difficult language to learn especially to non-native learners, teaching online has posed an even greater challenge to Mandarin language instructors. This study thus examines the use of a combination of platforms and applications online, customized to create an online learning system called ‘Pocket Mandarin’ to facilitate online Mandarin learning at the beginner level. The purpose is primarily to enable learning to take place in a fun and interactive manner by means of online flashcards, pronunciation, games and quizzes placed in a learning management system (LMS) plat-form called Padlet. To better understand how ‘Pocket Mandarin’ can effectively facilitate online teaching and learning among Mandarin as a foreign language (MFL) basic learners at the tertiary level, a survey was applied and it consisted of five parts which are students’ motivation, students’ attitude, cognitive development, design and interface as well as expectations. An open-ended survey was also administered to further support the research. The results show that ‘Pocket Mandarin’ was positively accepted by the students who found the lessons motivating, up building, cognitively applicable, with exceptional design and interface and was better than their initial expectations. Thus, there is great potential for ‘Pocket Mandarin’ to be widely used at a greater scale.